The Impact of Emotional Intelligence and Conflict Resolution on Employees Well-Being - Mahar, Dr Shoukat Ali; Lashari, Dr Irfan Ahmed; Larik, Dr. Akhlaque Hussain; Channa, Dr Muhammad Asif; Lashari, Ashique Ali (ACADEMIA International Journal for Social Sciences, 2025)
This study examined how emotional intelligence (EI), and conflict management styles influence employee well-being in Pakistani commercial banks. Data was collected from ninety-one bank employees in Khairpur Mir’s, Sindh out of a total of 118 employees. The study analyzed how two EI dimensions (self-awareness, social awareness) and two conflict styles (avoiding, problem-solving) predict employees well-being. Descriptive statistics confirmed that our scales were reliable (Cronbach’s α ranged from .768 to .845). Correlation analysis showed that problem-solving and self-awareness were strongly positively related to well-being, while social awareness showed little relation in simple bivariate tests. In multiple regression, the model was highly significant (F (4,86) =3466.58, p<.001, R²=.994). Problem-solving conflict management style positively predicted employees well-being (β = .078, p = .049), as hypothesized. Surprisingly, avoiding conflict management style also showed a large positive effect on well-being (β = 1.613, p < .001), contrary to many prior studies. In contrast, social-awareness of others’ emotions did not improve well-being in the multivariate model, and self-awareness unexpectedly carried a small negative (non-significant) coefficient (β = –.014, p = .635). These results suggested that conflict resolution enhances employees’ well-being. In Pakistani banks where job security is fragile and hierarchical norms prevail avoiding conflict may temporarily reduce stress, even though it may be unsustainable in the long run.